Green computing knowledge among students in a Ugandan university - Semakula, Isa; Samsuri, Suhaila (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Humans, including students, are partly responsible for rising levels of global warming through unsustainable computing practices. It is imperative that students participate in the global drive to reduce global warming through activities like green computing which advocates for sustainable use of computing resources to reduce energy consumption and carbon emissions. The study was conducted to establish green computing awareness levels of students from Islamic University in Uganda (IUIU) and also determine if such levels were influenced by computer experience. Results from a purposive sample of 452 students indicated that students’ levels of green computing awareness were low, and computer experience influenced two of the three dimensions of perceived knowledge of green computing